2014
DOI: 10.1155/2014/492956
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1Arg399Gln and Arg194Trp Polymorphisms and Risk of Systemic Lupus Erythematosus in an Iranian Population: A Pilot Study

Abstract: Background. Evidences are suggesting that DNA damage is implicated in development of systemic lupus erythematosus (SLE). Therefore we focused on two common XRCC1 polymorphisms (Arg399Gln and Arg194Trp) in SLE susceptibility in South East of Iran. Methods. Peripheral blood DNA was extracted from 163 SLE patients and 180 healthy controls. PCR-restriction fragment length polymorphism method was used for genotyping of XRCC1 Arg399Gln and Arg194Trp polymorphisms. Results. The frequency of Arg/Gln genotype of the XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Moreover, viral infections, drugs, chemicals, and exposure to ultraviolet (UV) radiation are also considered as potential environmental factors of SLE (Parks et al, 2005;Doria et al, 2008). Family and genetic studies, for example, monozygotic and dizygotic twins, indicate that genetic predisposition contributes to the development of SLE; therefore, numerous studies identified the relationship between different genetic variants and SLE susceptibility (Aringer and Hiepe, 2011;Bahrehmand et al, 2012;Nakou et al, 2013;Salimi et al, 2014). Furthermore, excessive DNA damage in SLE patients, besides the accumulation of nucleoproteins, may produce immunogenic antigens, which lead to the production of self-reactive antibodies (Abs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, viral infections, drugs, chemicals, and exposure to ultraviolet (UV) radiation are also considered as potential environmental factors of SLE (Parks et al, 2005;Doria et al, 2008). Family and genetic studies, for example, monozygotic and dizygotic twins, indicate that genetic predisposition contributes to the development of SLE; therefore, numerous studies identified the relationship between different genetic variants and SLE susceptibility (Aringer and Hiepe, 2011;Bahrehmand et al, 2012;Nakou et al, 2013;Salimi et al, 2014). Furthermore, excessive DNA damage in SLE patients, besides the accumulation of nucleoproteins, may produce immunogenic antigens, which lead to the production of self-reactive antibodies (Abs).…”
Section: Introductionmentioning
confidence: 99%
“…DNA repair genes can contribute to SLE predisposition (Herrick et al, 1995), and polymorphisms of XRCC1, XRCC3, and XRCC4 genes are associated with manifestation of SLE Lin et al, 2009;Warchol et al, 2012;Salimi et al, 2014). Moreover, there are numerous variants in XRCC5, XRCC6, and XRCC7 genes, which have been associated with different diseases, such as gastric cancer (Lim et al, 2002), head and neck cancer (Chang et al, 2006), breast cancer (Fu et al, 2003), glioma (Wang et al, 2004), and AML (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that genetic factors play a key role in this disease (2)(3)(4)(5). Anti-genicity could be increased by reactive oxygen species (ROS), which causes DNA conformation changes and DNA base damages or breaks (6). DNA repair enzymes monitor the DNA structure to correct damaged nucleotide produced by methylation, oxidation or oxidative damage; therefore, DNA repair mechanisms have an essential role in genome stability (7).…”
mentioning
confidence: 99%
“…Other investigations by Lin et al and Warchol et al showed that Arg/Arg genotype of rs25487 had a protective role against SLE in Chinese and Polish populations (8,11). In the Iranian population, only one investigation was done, in which Salimi et al showed that Arg/Gln had a protective role against SLE (6). Another SNP (rs1799782) was explored in 2 studies, which showed no association between the related SNP and SLE susceptibility (6,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation